Multivariate statistical analysis of morpho-anatomical data of nine sect. Caulopterae species (Baccharis – Asteraceae) used in folk medicine - Martínez, María Laura (2018)
Baccharis species belonging to sect. Caulopterae are difficult to identify. Most countries are controlling the quality of herbal medicines destined for the internal market or export. “Carquejas” are used arbitrarily for the same medicinal purposes and only three species of sect. Caulopterae are official herbal medicines. In the present study, a morpho-anatomical and statistical analysis was performed with nine species of sect. Caulopterae: Baccharis articulata, B. crispa, B. gaudichaudiana, B. microcephala, B. penningtonii, B. phyteumoides, B. sagittalis, B. triangularis and B. trimera, emphasizing the importance of anatomy as a taxonomic tool. A total of 114 populations of these nine species were examined. The first three principal components of morphoanatomical data provided relevant information to classify the species (75.04% of the total variability). The most discriminatory variable in this issue was the stomatal index (1.0530). We determined the qualitative and quantitative variables in order to differentiate the species by using principal components analysis and ANOVA tests. Stomata type, uniseriate trichome type and presence/absence of collenchyma in the wing margin are the qualitative variables that should be analyzed. Regarding quantitative variables, the epidermal ones in superficial view are more important and discriminatory than those of alate stem cross section and they must be considered for proper quality control of the species of this work.